Biophysical characteristics of gap junctions in vascular wall cells: implications for vascular biology and disease - Brink,P.R. (2000)
The role gap junction channels play in the normal and abnormal functioning of the vascular wall is the subject of much research. The biophysical properties of gap junctions are an essential component in understanding how gap junctions function to allow coordinated relaxation and contraction of vascular smooth muscle. This study reviews the properties thus far elucidated and relates those properties to tissue function. We ask how biophysical and structural properties such as gating, permselectivity, subconductive states and channel type (heteromeric vs homotypic vs heterotypic) might affect vascular smooth muscle tone.